Gender and German colonialism
1 online resource (xi, 332 pages)
Keywords: "This book addresses the intersection between gender and colonialism primarily in German colonialism. Gender and German Colonialism is concerned with colonialism as a historical phenomenon and with the repercussions and transformations of the colonial era in contemporary racist and sexist discourses and practices relating to refugees, migrants, and people of non-European descent living in Europe. This volume contributes to the broader effort of decolonization with particular attention to concepts of gender. Rather than focus on only one European empire, it discusses and compares multiple former colonial powers in context. In addition to German colonialism, some chapters focus on the role of gender in Dutch and Belgian colonialism in Indonesia, Africa, and the Americas. This volume will be of value to students and scholars interested in women's and gender studies, social and cultural history, and imperial and colonial history"--